2021
DOI: 10.1039/d0cy01533d
|View full text |Cite
|
Sign up to set email alerts
|

In situprobing of Pt/TiO2activity in low-temperature ammonia oxidation

Abstract: NAP-XPS and operando XAS study of Pt/TiO2 catalysts shows that Pt0 species stabilized on TiO2 surface have the highest activity at low-temperature NH3 oxidation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 86 publications
2
41
0
Order By: Relevance
“…This phenomenon is related to the amount of Pt deposited directly on the TiO 2 nanotubes. Because Pt sputtering time was short (30 s), the small amounts of Pt nanoparticles were coated on the surface of the TiO 2 nanotubes (Figure 1), and these nanoparticles are likely to be easily oxidized to form PtO X structures [28,29]. Thus, the new binding peak (~72.5 eV) was expected to be the Pt-O bond generated by binding Pt metals to the TiO 2 nanotubes in a short time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon is related to the amount of Pt deposited directly on the TiO 2 nanotubes. Because Pt sputtering time was short (30 s), the small amounts of Pt nanoparticles were coated on the surface of the TiO 2 nanotubes (Figure 1), and these nanoparticles are likely to be easily oxidized to form PtO X structures [28,29]. Thus, the new binding peak (~72.5 eV) was expected to be the Pt-O bond generated by binding Pt metals to the TiO 2 nanotubes in a short time.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a new peak at 72.5 eV was detected in the Pt 4f spectra of the PtAu30. This peak seemed to be the formation of Pt-O bonds when a small amount of Pt was first coated at the surface of the TiO 2 nanotubes [28,29].…”
Section: Xps Analysismentioning
confidence: 99%
“…For example, intermediate formation and/or dynamic electron donation can be better investigated by in situ XPS characterization. The catalytic mechanism of ammonia oxidation over Pt catalysts was studied via in situ XPS by Boronin et al 106 and Nieuwenhuys et al 107 They observed dehydrogenation intermediates (NH x , x = 0, 1, 2) and changes of active sites. It is envisaged that similar information (e.g., detection of NH 2ad , NH ad , and N ad ) could be obtained by using in situ XPS in the investigation of catalytic ammonia decomposition.…”
Section: Perspectivesmentioning
confidence: 99%
“…For example, intermediate formation and/or dynamic electron donation can be better investigated by in situ XPS characterization. The catalytic mechanism of ammonia oxidation over Pt catalysts was studied via in situ XPS by Boronin et al and Nieuwenhuys et al . They observed dehydrogenation intermediates (NH x , x = 0, 1, 2) and changes of active sites.…”
Section: Perspectivesmentioning
confidence: 99%
“…Nevertheless, under reaction conditions, at least 40% of Pt surface remains oxidized resulting in the formation of N 2 O [29]. Otherwise, the metal-support interactions of Pt/TiO 2 were reported to stabilize Pt in the metallic state (also under reaction conditions) [30]. The Pt 0 content can also be manipulated by preparation procedure of Pt/SiO 2 -Al 2 O 3 , i.e., by adding ascorbic acid (vitamin C, vC; n(vC)/n(Pt) = 0.25-1.5) [31].…”
Section: Pt-and Pd-based Catalystsmentioning
confidence: 99%